Role of TGF-β Pathway Polymorphisms in Sporadic Thoracic Aortic Aneurysm: rs900 TGF-β2 Is a Marker of Differential Gender Susceptibility. (24th February 2014) - Scola, Letizia; Di Maggio, Federica M.; Vaccarino, Loredana; Bova, Manuela; Forte, Giusy I.; Pisano, Calogera; Candore, Giuseppina; Colonna-Romano, Giuseppina; Lio, Domenico; Ruvolo, Giovanni; Balistreri, Carmela R.
Abstract : Thoracic aortic aneurysm (TAA) is a progressive disorder involving gradual dilation of ascending and/or descending thoracic aorta with dissection or rupture as complications. It occurs as sporadic or defined syndromes/familial forms.Genetic, molecular and cellular mechanims of sporadic TAA forms are poorly characterized and known. Thus, our interest has been focused on investigating the role of genetic variants of transforming growth factor- β (TGF- β ) pathways in TAA risk. On the other hand, no data on the role of genetic variants of TGF- β pathway in sporadic TAA exist until now. In addition, other cytokines, including IL-10, orchestrate TAA pathophysiology. Their balance determines the ultimate fate of the aortic wall as healing atherosclerosis or aneurysm formation. Thus, in this paper it was analyzed the role of ten polymorphisms of genes encoding TGF- β isoforms and receptors, and IL-10 in sporadic TAA. Our study included cases affected by sporadic TAA and two control groups. The most relevant finding obtained allows us to propose that rs900 TGF- β 2 SNP is associated with sporadic TAA in women. This might open new perspectives for the analysis of sporadic TAA susceptibility factors and prevention.